Higher patient knowledge and resilience improve the functional outcome of primary total knee arthroplasty - Bumberger, Alexander; Borst, Katharina; Hobusch, Gerhard M.; Willegger, Madeleine; Stelzeneder, David; Windhager, Reinhard; Domayer, Stephan; Waldstein, Wenzel (Wiener Klinische Wochenschrift, 2021)
Summary Background A significant percentage of patients have an unfavorable outcome following primary total knee arthroplasty (TKA). This study aimed to evaluate whether specific knowledge about the implant and resilience can influence the functional outcome following TKA. Methods A consecutive series of 163 patients following primary TKA at a mean age of 70 years (SD 9.1 years) were included at a regional rehabilitation center between December 2015 and December 2016. Specific patient knowledge (scale 0–7), Connor Davidson Resilience Scale (CD-RISC), Western Ontario and McMaster Universities (WOMAC) score, University of California and Los Angeles (UCLA) score and constitutional parameters were assessed on admission. Pearson’s correlation analysis and stepwise linear regression analysis were performed to investigate associations between knowledge, resilience and functional scores. Results The mean overall knowledge score was 3.5 out of 7 and the mean resilience score was 72.9 out of 100. Mean WOMAC and UCLA scores on admission were 23.8 and 5.5, respectively. Stepwise linear regression analysis identified knowledge and age as significant predictors of WOMAC scores (R 2 = 14.3%, p = 0.003). Knowledge and resilience were identified as significant predictors of UCLA scores (R 2 = 13.8%, p = 0.013). Conclusion This study highlights the importance of patient-related factors as part of an integral patient care concept in TKA. Although the identified predictors still need to be refined, it could be demonstrated how better patient knowledge might ultimately lead to better functional outcome following TKA. Routinely assessing patients’ resilience might be a useful tool to identify patients at risk for low activity levels. Level of evidence III. Patient-reported outcome study.